Development of a Prognostic Nomogram in Hepatocellular Carcinoma with Portal Vein Tumor Thrombus Following Trans-Arterial Chemoembolization with Drug-Eluting Beads - Cheng S; Yu X; Liu S; Jin Z; Xue H; Wang Z; Xie P (Cancer Management and Research, 2021)
Sihang Cheng,1,2 Xiang Yu,2 Siyun Liu,3 Zhengyu Jin,1 Huadan Xue,1 Zhiwei Wang,1 Ping Xie2 1Department of Radiology, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences, Beijing, People’s Republic of China; 2Department of Radiology, Sichuan Provincial People’s Hospital, Sichuan Academy of Medical Sciences, Chengdu, People’s Republic of China; 3Pharmaceutical Diagnostics, GE Healthcare, Beijing, People’s Republic of ChinaCorrespondence: Zhiwei Wang; Ping Xie Tel +8610 69159562; +8628 87393976Email zhiweiwang1981@sina.com; haoyanx@163.comObjective: To develop and validate a prognostic nomogram in eastern patients with hepatitis B virus (HBV)-associated hepatocellular carcinoma (HCC) and portal vein tumor thrombus (PVTT) receiving trans-arterial chemoembolization with drug-eluting beads (DEB-TACE).Methods: This retrospective study included 200 patients with training cohort (n = 118) from institution 1 and test cohort (n = 82) from institution 2. All these patients received first-line DEB-TACE between October 2016 and October 2018. Multivariate Cox proportional hazard regression analysis was performed on the training cohort to reveal the independent prognostic factors, and then prognostic nomograms were developed. In order to evaluate the performance of the nomogram comprehensively in both the training and test cohorts, C-index, Kaplan–Meier curve with Log rank test, receiver operating characteristic curve (ROC), calibration plot, and decision curve analysis (DCA) were performed.Results: Tumor number, serum γ-glutamyl transferase (GGT) level, and level of PVTT were independent risk factors of prognosis. A nomogram was constructed to predict 6-, 12- and 18-month overall survival (OS) based on these identified prognostic factors. C-indexes of the nomogram were 0.88 (95% confidence interval [CI], 0.79– 0.97) in the training cohort and 0.87 (95% CI, 0.75– 0.99) in the test cohort. The Kaplan–Meier curve analysis showed that the nomogram was able to separate patients into low- and high-risk subgroups. ROC curves for the nomogram at 6-, 12- and 18-month showed satisfied discrimination, with an AUC of 0.765, 0.803 and 0.809 in the training cohort, respectively, and 0.772, 0.724 and 0.746 in the test cohort, respectively. The calibration curve demonstrated good agreement between predicted and actual survival rates in the training and test cohorts. The decision curve showed good performance of the nomogram in terms of clinical application.Conclusion: We developed and validated a nomogram that was accurate and clinically useful in eastern patients with HBV-associated HCC with PVTT who underwent DEB-TACE.Keywords: hepatocellular carcinoma, portal vein tumor thrombus, trans-arterial chemoembolization, drug-eluting beads, nomogram